A Female Voice for Action in the Tragicomedia de Calisto y Melibea - Connie L. Scarborough (Medievalia, 2022)
Although most critical attention on laments for the dead in the Tragicomedia de Calisto y Melibea has focused on Pleberio’s long lament for Melibea in Auto XXI, Elicia’s lament for the loss of her lover, Sempronio, his companion, Pármeno, and her protector, Celestina, is highly significant for plot development. Her lament is a decisive event that sets in motion a plan for revenge that will ultimately lead to the deaths of Calisto and Melibea. This article demonstrates how Elicia’s personal experience of loss brings about significant changes in her characterization. With the help of Areúsa, Elicia hatches a plan for vengeance on the aristocratic lovers that she despises. Building on Louise Haywood’s studies of female laments for the dead, it examines Elicia’s curse on Calisto and Melibea and shows how her words have real and tragic consequences. In Rojas’s world, a prostitute’s expression of grief is a force strong enough to topple the elites of society and fundamentally contribute to the tragedia embedded in his work’s hybrid title.